2018
DOI: 10.1371/journal.pone.0193549
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, sleep characteristics, and comorbidities in a population at high risk for obstructive sleep apnea: A nationwide questionnaire study in South Korea

Abstract: ObjectiveTo determine the prevalence, sleep characteristics, and comorbidities associated with a high risk for obstructive sleep apnea (OSA) in the Korean adult population.MethodsWe analyzed data from 2,740 subjects who responded to a nationwide questionnaire survey of sleep characteristics. Those who qualified under two or more symptom categories of the Berlin questionnaire were defined as “at high risk for OSA”. We investigated their socio-demographic information, sleep habits, and medical and psychiatric co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 72 publications
5
23
2
Order By: Relevance
“…Thus, our data support the hypothesis that the prevalence estimates for no, mild, or moderate sleep apnea among those with STOP-Bang scores of 3 and 4 may be evenly balanced [37] and that STOP-Bang threshold at 4 may be more useful in the general population [38]. This may partially explain a somewhat higher rate of sleep apnea with a cut-off value at ≥3 (34.2%) in our study population compared to other studies [39]. …”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, our data support the hypothesis that the prevalence estimates for no, mild, or moderate sleep apnea among those with STOP-Bang scores of 3 and 4 may be evenly balanced [37] and that STOP-Bang threshold at 4 may be more useful in the general population [38]. This may partially explain a somewhat higher rate of sleep apnea with a cut-off value at ≥3 (34.2%) in our study population compared to other studies [39]. …”
Section: Discussionsupporting
confidence: 85%
“…Also similar to our results, the association of BMI and some of mental component dimensions of HRQoL were found in OSA patients [ 55 ]. Evidence indicate that BMI and depression may contribute to sleep difficulties [ 34 , 39 , 56 ]. Our data also showed that depression symptoms were significantly higher in subjects with poor sleep quality, daytime sleepiness, OSA risk, and insomnia, which was to be expected.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest that breaking every 4 hours should be practiced to prevent drowsy-related accidents. High risk of OSA in the BQ was reported in 57.3% of participating CMV drivers, higher compared with 19.8% of the general male population of Korea [30]. This proportion is consistent with results of recent studies reporting prevalence of suspected OSA in CMV drivers ranging between 26% and 56% [31][32][33].…”
Section: Discussionsupporting
confidence: 90%
“…Our survey also did not collect information on sleep quality [ 44 ] and sleep disorder [ 45 ] and thus we were not able to account for these variables in our analysis. Individuals with sleep disorder such as sleep apnea and insomnia are more likely to have shorter sleep duration [ 46 , 47 ] and higher risk of all-cause mortality [ 46 – 50 ]. Therefore, failure to take account of diagnosis and treatment of sleep disorder may lead to overestimation of positive association between short sleep and mortality.…”
Section: Discussionmentioning
confidence: 99%